Analysis of Structural Theory in Economic and Social Tensions: Guatemala Country Case Study - Antonio Fernandez Calisto (ENDLESS: INTERNATIONAL JOURNAL OF FUTURE STUDIES, 2023)
One of the relevant issues in the field of studies into not-for-profit organizations is to understand the singular characteristics of this organizational phenomenon. In this work we have turned to the basis of the Structuration Theory for analyzing such organizatiosn. We propose that its contribution to the advance of knowledge in this field is its use of the concept of structural processes, prepared from work originally done by British sociologist, Anthony Giddens. The conceptual framework identiefis and analyses the ideas contained in the main theoretical perspectives found in academic works on Social Economics and not-for-profit organizations (NPO). This work makes a double contribution: by means of a case study, it offers empirical experience that takes a structuration analytical approach, and moves forward the discussion on singlaur characteristics of not-for-profit organizations as an organizational phenomenon, which increased during the last two decades of the XXth century. The concept of structuration processes allows for the analysis of organizational paradoxes and conflicts, taking the structure not as a stiac object that defines the restrictions to action or limits the scope of authority, but as an abstraction that reveals how the rules and resources oaf social system relate with each other in a process defined by Giddens as the duality of structure.